Research of the Usage of Double-fed Generators in Wind Turbines - Ramonas, Č.; Kepalas, V.; Adomavičius, V. (Elektronika ir Elektrotechnika, 2009)
Results of researches of the wind turbine with double-fed generator when its stator is fed from the DC power source are described in the paper. Usually stator and rotor of the wind turbine’s double-fed generator is connected with electric grid over the electronic converters. If capacity of wind turbine is not considerable, application of the generator’s exciting over the stator’s windings can be acceptable and justified in order of simplification of wind power conversion system. Only one converter is used in this case for connection of the rotor circuit with electric grid. Equivalent scheme and equations, which can be used for calculation of parameters of the power supplied into electric grid depending on the wind speed, are given in the paper. Electromagnetic processes for the intervals of operation, shorting and inverting are described by means of the system of differential equations. Mathematical model of the wind power conversion system is based on this system. Load of the wind turbine and pulse-width mode of operation of the inverter are taken into consideration. Results of the research showed the possibility to keep the wind turbine’s operation on the maximum available power depending on the wind speed. However, the inverted current has a pulse shape. Therefore the filters should be used after the inverter in order to make the inverted current closer to the sine wave. Ill. 6, bibl. 8 (in English, summaries in English, Russian and Lithuanian).